Neurorrhaphy in Presence of Polyethylene Glycol Enables Immediate Electrophysiological Conduction in Porcine Model of Facial Nerve Injury - Petrov, Dmitriy; Burrell, Justin C.; Browne, Kevin D.; Laimo, Franco A.; Roberts, Sanford E.; Ali, Zarina S.; Cullen, D. Kacy (Frontiers in Surgery, 2022)
Facial nerve trauma often leads to disfiguring facial muscle paralysis. Despite several promising advancements, facial nerve repair procedures often do not lead to complete functional recovery. Development of novel repair strategies requires testing in relevant preclinical models that replicate key clinical features. Several studies have reported fusogens, such as polyethylene glycol (PEG), can improve functional recovery by enabling immediate reconnection of injured axons; however, these findings have yet to be demonstrated in a large animal model. We first describe a porcine model of facial nerve injury and repair, including the relevant anatomy, surgical approach, and naïve nerve morphometry. Next, we report positive findings from a proof-of-concept experiment testing whether a neurorrhaphy performed in conjunction with a PEG solution maintained electrophysiological nerve conduction at an acute time point in a large animal model. The buccal branch of the facial nerve was transected and then immediately repaired by direct anastomosis and PEG application. Immediate electrical conduction was recorded in the PEG fused nerves (n=9/9), whereas no signal was obtained in a control cohort lacking a calcium chelating agent in one step (n=0/3) and in the no PEG control group (n=0/5). Nerve histology revealed putative fused axons across the repair site, whereas no positive signal was observed in the controls. Rapid electrophysiological recovery following nerve fusion in a highly translatable porcine model of nerve injury supports previous studies suggesting neurorrhaphy supplemented with PEG may be a promising strategy for severe nerve injury. While acute PEG-mediated axon conduction is promising, additional work is necessary to determine if physical axon fusion occurs and the longer term fate of distal axon segments on functional recovery.